Identification of heat-responsive genes in carnation (Dianthus caryophyllus L.) by RNA-seq - Wan, Xueli; Zhou, Qiao; Wang, Yuanyuan; Wang, Wenen; Bao, Manzhu; Zhang, Junwei (Frontiers in Plant Science, 2015)
Carnation (Dianthus caryophyllus L.) is an important flower crop, having substantial commercial value as a cut-flower due to the long vase-life and wide array of flower colours and forms. Standard carnation varieties perform well under cool climates but are very susceptible to high temperatures which adversely affect the yield and the quality of the cut-flowers. Despite several studies of carnation contributing to the number of expressed sequence tags (ESTs), transcriptomic information of this species remains very limited, particularly regarding abiotic stress-related genes. Here, transcriptome analysis was performed to generate expression profiles of heat stress (HS)-responsive genes in carnation. We sequenced a cDNA library constructed with mixed RNA from carnation leaves subjected to 42oC HS (0, 0.5, 1 and 2 h) and 46oC HS (0.5, 1 and 2 h), and obtained 45,604,882 high quality paired-end reads. After de novo assembly and quantitative assessment, 99,255 contigs were generated with an average length of 1053bp. We then obtained functional annotations by aligning contigs with public protein databases including NR, SwissProt, KEGG and COG. Using the above carnation transcriptome as the reference, we compared the effects of high temperature treatments (42oC: duration 0.5, 2 or 12h) delivered to aseptic carnation seedlings, relative to untreated controls, using the FPKM metric. Overall, 11,471 genes were identified which showed a significant response to one or more of the three HS treatment times. In addition, based on GO and metabolic pathway enrichment analyses, a series of candidate genes involved in thermo-tolerance responses were selected and characterized. This study represents the first expression profiling analysis of D. caryophyllus under heat stress treatments. Numerous genes were found to be induced in response to HS, the study of which may advance our understanding of heat response of carnation.